Development of RAPD Random Amplified Polymorphic DNA Markers for Authentification of Limnophila heterophylla Roxb Benth - RH, Padiya (International Journal of Pharmaceutical & Biological Archive, 2013)
Development of RAPD Random Amplified Polymorphic DNA Markers for Authentification of Limnophila heterophylla Roxb Benth